Hygienic and nutritional habits in dental caries prevention in 5-year-old children from Biala Podlaska - Elżbieta Huk-Wieliczuk; Anna Czeczuk (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. Preschool children are particularly susceptible to dental caries development. Due to the fact that deciduous teeth are less mineralised, they are more likely to be affected by this condition. Therefore, preschool age is a significant period in shaping positive health-oriented attitudes regarding dental caries prevention. Objective. The aim of this study was to analyse hygienic and nutritional habits in children aged 5 from Biala Podlaska in the context of dental caries prevention. Material and Method. The study included 454 preschool children (251 boys and 203 girls) from Biala Podlaska. Their hygienic and nutritional habits were examined with a diagnostic survey using the authors' own anonymous questionnaire. Mean consumption of nutrients (calcium, phosphorus and vitamin D) was estimated on the basis of average daily consumption calculated as a mean from three 24-hour interviews (conducted by the authors in a kindergarten or at children's houses). A nutritional value of a daily portion was calculated with the use of "Dieta 5.0" software (National Food and Nutrition Institute). Results. Research results revealed that in the case of only one in three children, parents began toothbrushing within the first year of a child's life. Approximately 90% of preschool children brushed their teeth at least twice a day. Half of the children under examination brushed their teeth for 1-2 minutes usually with a traditional toothbrush. Toothbrushing was supervised by 62.5% of the boys' parents and 38.9% of the girls' parents (p<0.05). Almost 66% of the parents took their children to a dentist for regular (once or twice a year) dental check-ups. Analyses of daily food rations revealed insufficient amounts of calcium (25%) and vitamin D (over 80%). Moreover, an excessive intake of phosphorus (twice as high as the norm) was noted. Conclusions. Developing appropriate hygienic and nutritional habits in children is an indispensable element in the prevention of lifestyle diseases, including dental caries.